A tájhasználat változása a Hódmezővásárhelyi kistérségben a földhasználat és a felszínborítás változásának tükrében - Kis, Krisztián (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The proportion of the land use categories reflects the quality and intensity of the landscape use. According to the data the land use of the micro-region mostly defined by arable land, grassland (meadow/pasture), forest and uncultivated land, which are amounted to 99% of the area of the micro-region during the examined period. In spite of the short examined period it can be concluded from the examination that considerable changes took place in the landscape use of the micro-region which can be derived from the land use and land cover changes. It can be assessed as favourably change that forest areas increased but the increase of uncultivated land at the same time can be less favourable assessed. The proportion of forest and semi-natural areas, wetlands and water bodies also increased as the positive result of the land use change.